Production Factors of Macaroni Borneo Snack Business in Banjarmasin City - Nazlatusyifa Riswanda; Mutiani Mutiani; Raihanah Sari; Syarifuddin Syarifuddin; Fatwa Nur’aini (Universitas Lambung Mangkurat, 2026)
The snack food business Macaroni Borneo in Banjarmasin City has grown quite rapidly amid the high public interest in local snacks. However, this growth cannot be separated from production-related issues, especially in managing production factors that determine business continuity and sustainability. This study focuses on analyzing production factors, including labor, capital, raw materials, and the role of entrepreneurship in the production activities of Macaroni Borneo. The purpose of this research is to understand how each production factor is managed and to what extent these factors influence production capacity and continuity. The method used is descriptive qualitative, with data collected through direct observation at the business location, interviews with the owner and workers, and supporting documentation. The results show that Macaroni Borneo’s production is strongly influenced by the stability of raw materials, which still partly depend on suppliers from outside the region, limitations in labor at certain production stages, and capital management that is still carried out gradually. On the other hand, the owner’s entrepreneurial role becomes a key factor in keeping production running through flavor innovation, adjustments in production capacity, and adaptive decision-making. These findings indicate that business success is not solely determined by the amount of capital, but by the ability to manage production factors effectively in response to market conditions.